The damned and the dead : the Eastern Front through the eyes of Soviet and Russian novelists - Ellis, Frank, 1953- (Modern war studies., 2011)
"The confrontation between the Wehrmacht and the Red Army on the Eastern Front of World War II was defined by incalculable suffering, destruction, casualties, and heroism. While many historians have chronicled the epic nature of that arena of war, it has largely been left to Russian novelists to fully express the intense human dimensions of that conflict. Frank Ellis's groundbreaking study provides the first comprehensive survey of that impressive body of literature. Canvassing a wide spectrum of works by Soviet and post-Soviet writers, many of whom were war veterans themselves, Ellis uncovers themes both common to war literature in general and distinctive to the Soviet experience ... One of the many threads running throughout Ellis's study is the dilemma of the Red Army soldier condemned to serve a regime that was utterly paranoid regarding the allegiances of its own armies, so much so that Soviet soldiers often felt as threatened by the Soviet government as they did by the German armies. Many of these novels reinforce the now well known fact that Stalin devoted considerable resources to ferreting out soldiers whose actions (or inactions) suggested disloyalty to his repressive regime. A few of them ... became battlegrounds in their own right, pitting Soviet writers against Soviet censors in a struggle over the public memory of the war. Russia's memories of World War II are forever tied to the suffering of its people. Ellis's rich and revealing work shows us why."--Jacket